Perlakuan Akuntansi Revaluasi Aset Tetap Pada PT Pos Indonesia (Persero) - Ahmad Kudhori; Nur Fitriah (Universitas Merdeka Madiun, 2020)
Abstractâ€” PSAK No. 16/2015 states that the fixed assets owned by an entity will initially be recognized according to their acquisition costs and will be depreciated annually. Fixed assets which have been recognized will be measured by two methods, namely the cost method and revaluation method. Revaluation method is carried out with the aim to present the true value of fixed assets. Revaluation method is done by finding the difference in value of fixed assets before and after revaluation. This research was carried out by recognizing, measuring, and presenting revalued fixed assets. Fixed assets that are recognized are land and building groups, machinery, motor vehicles, office equipment and will be depreciated using the straight-line method and declining balance. The results of this study are an increase in the value of the fixed assets of PT Pos Indonesia (Persero) Magetan 63300 Post Office, worth Rp20,158,558.00. The addition of this fixed asset value is called a revaluation surplus or revaluation profit of assets that will be presented in other comprehensive income in the statement of profit or loss and other comprehensive income.Â Keywordsâ€”: Fixed Assets; Depreciation; Cost Method; Revaluation Method.